The Effect of Eight Weeks Resistance Training on Leptin and Insulin Resistance in Obese Female - Soraya Khalili; Reza Nouri (پزشکی بالینی ابن سینا, 2013)
Introduction & Objective: Leptin , the main peptide secreted by adipose tissue, is considered an alarming factor in the regulation of body fat content . With regard to the physiological effect of exercise as one of the potential regulators of leptin secretion from adipose tissue , this study was performed to examine the effects of resistance exercise on leptin.